A quantified Kraljic Portfolio Matrix: Using decision analysis for strategic purchasing. Issue 3 (June 2018) - Montgomery, Robert T.; Ogden, Jeffrey A.; Boehmke, Bradley C.
Abstract: Since its inception, the Kraljic Portfolio Matrix (KPM) has been widely used as a diagnostic and prescriptive purchasing tool. One of the primary weaknesses of the KPM is the qualitative nature of the model, which results in a subjective method for weighting and positioning suppliers or commodities in the various quadrants. In an effort to help overcome this widely cited weakness, this research proposes an objective, quantitative decision analysis approach to position products and services within the KPM. Single attribute value functions are used to quantify the strategic purchasing attributes of the KPM. A multi attribute value function is then used to quantify and rank-order products and services within the KPM based on the two strategic purchasing objectives. We empirically demonstrate this approach using data from an organization with a 10 billion purchasing portfolio. Furthermore, we illustrate how a cost-benefit view of the results help decision makers quickly and easily identify the products and services most conducive to the implementation of commercial best practice purchasing strategies. A sensitivity analysis advocates the robustness of our approach. Highlights: Decision analysis approach to position products and services in the Kraljic matrix. Leverages value functions to quantify and rank order purchasing attributes. Cost benefit analysis to identify products and services for strategic purchasing. Exemplar analysis on an organization with a 10 billion purchasing portfolio.